Delayed Primary Repair of Complex Duodenal Injury Associated to Multiorgan Failure Due to Blunt Abdominal Trauma - Aceves-Ayala, José Miguel; Noriega-Velásquez, Allan Josué; Briceño-Fuentes, Alberto; Ortiz-Orozco, Cesar Alberto; Rojas-Solís, Pablo Francisco; Rivas-Quezada, Pedro Xavier; Bautista-López, Carlos Alfredo (The Surgery Journal, 2023)
Duodenal injuries are rare and difficult to diagnose, with an incidence between 1 and 5% in cases of abdominal trauma. We present the case of a 30-year-old man who suffered a motorcycle collision presented with a 24-hour history of abdominal pain, peritoneal tenderness, and hemodynamic instability. Imaging studies show evidence of free fluid in the perihepatic, perisplenic, and pelvic space. An exploratory laparotomy was performed, finding a grade III duodenal, grade V jejunal, and grade II pancreatic injuries. The basis of surgical treatment being a primary anastomosis of duodenal and jejunal injuries, which allowed discharging him home 8 days after surgery and without any complications in his follow-up.
Keywords: duodenal trauma; AAST (American Association for the Surgery of Trauma); rhabdomyolysis; hyperkalemia; anastomosis